2021
DOI: 10.1002/chem.202100739
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel‐Stiffening and Non‐Cell Adhesive Properties of Amphiphilic Peptides with Central Alkylene Chains

Abstract: Amphiphilic peptides bearing terminal alkyl tails form supramolecular nanofibers that are increasingly used as biomaterials with multiple functionalities. Insertion of alkylene chains in peptides can be designed as another type of amphiphilic peptide, yet the influence of the internal alkylene chains on self-assembly and biological properties remains poorly defined. Unlike the terminal alkyl tails, the internal alkylene chains can affect not only the hydrophobicity but also the flexibility and packing of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…After title and abstract screening, 156 articles remained for full-text inspection. From the 156 articles assessed for eligibility, 23 articles were excluded due to the following reasons: in 11 articles, the full text was not retrieved [20][21][22][23][24][25][26][27][28][29][30], 4 articles were not related to the dentistry field [31][32][33][34], 4 studies were reviews [6,12,35,36], 3 studies were not related to peptides [37][38][39], and 1 study was a pilot clinical trial [40]. Thus, a total of 133 articles were included in the present review.…”
Section: Resultsmentioning
confidence: 99%
“…After title and abstract screening, 156 articles remained for full-text inspection. From the 156 articles assessed for eligibility, 23 articles were excluded due to the following reasons: in 11 articles, the full text was not retrieved [20][21][22][23][24][25][26][27][28][29][30], 4 articles were not related to the dentistry field [31][32][33][34], 4 studies were reviews [6,12,35,36], 3 studies were not related to peptides [37][38][39], and 1 study was a pilot clinical trial [40]. Thus, a total of 133 articles were included in the present review.…”
Section: Resultsmentioning
confidence: 99%
“…Chensinin-1b, an antimicrobial peptide, has been conjugated to an alkyl tail (C8, C12, or C16), as reported by Dong et al, to create an amphiphile sequence containing chensinin-1b peptide that self-assembles into a micellar structure in aqueous solution with cell penetration ability and up to seven-fold anti-cancer activity by the incorporation of the aliphatic acids [136]. Unlike the tailinsertion of the alkyl group, a recent study conducted by Yaguchi et al reported several peptide chains that contained centrally located alkylene groups of different lengths (C1, C2, C3, and C4) in the peptide via SPPS [137]. Comparing the physicochemical properties of those sequences, they found that the central alkylene chain allowed for strengthened hydrogen bonds in the antiparallel β-sheet stacks, in which the amphiphilic molecule showed great potential to selfassemble into nanofibers and stiff hydrogels with low cell adhesion.…”
Section: Amphiphilic Peptides With Alkyl Tails and Co-peptidesmentioning
confidence: 99%